Anatomical surgical study of the superficial veins of the forearm and elbow crease: Its interest in performing angioacces for chronic hemodialysis - Varela, Daniel; Regules, Elías; Ruiz Liard, Claudio; Rudnitzky, Omar; Crestanello, Francisco (Cirugía del Uruguay, 1986)
Study of the anatomy of superficial veins of the forearm in 140 dead body extremities with a view to the farmation of arteriovenous fistulae far hemodialysis. The radial superficial vein is the best suited for that purpose.